Consolidación y retos del movimiento mapuche / Consolidation and challenges of the mapuche movement - ALONSO REYNOSO, Carlos; ALONSO SÁNCHEZ, Jorge (Utopía y Praxis Latinoamericana, 2020)
RESUMEN Se hace un recorrido por la historia del pueblo Mapuche, los despojos y represiones que ha sufrido, las luchas que ha emprendido, sus organizaciones y las diversas opciones que se le presentan en la coyuntura del potente movimiento de protesta popular chilena a finales de 2019. Se plantea que la relación entre los pueblos en movimiento Mapuche, kurdo y zapatista puede impulsar una alternativa de autonomía desde abajo. ABSTRACT This is a revision of the history of the Mapuche people, the dispossessions and repressions they have suffered, the struggles they have undertaken, their organizations and the various options presented to them at the conjuncture of the powerful Chilean popular protest movement at the end of 2019. It is proposed that the relation between the Mapuche, Kurdish and Zapatista movements can promote an alternative for autonomy from below.